The Philosophy and Authentication of Welfare Equalization in the Islamic Economy - Aang Kunaifi; Fadali Rahman; Risca Dwiaryanti (Perhimpunan Intelektual Muslim Indonesia, 2021)
The promise of the welfare of the capitalist economic system initiated three centuries ago is only realized for the owners of capital. Even in 2017 in The Great Devide, Joseph E. Stigliz reported increasingly alarming data that the wealth of 1% of the world's population is equivalent to 99% of the world's population. This article aims to describe: (1) The concept and philosophical value of welfare in Islam, and (2) historical authentic evidence of the creation of welfare in Islam. To obtain representative and comprehensive data, this article is compiled based on primary and secondary data. The Central Bureau of Statistics reports economic developments regarding the development of people's welfare in Indonesia and reports from world institutions such as the IMF, World Bank, as a comparison of global economic conditions. The data is then discussed under ideal conditions recorded in the golden history of Islam to find that prosperity in an Islamic economy is capable of being realized. The contribution of articles among scientific studies that discuss welfare is about concrete explanations or clear standards of welfare attainment. Namely, the nominal wealth to be called prosperous, an applicative and systematic method of achievement, and the affirmation that the Islamic economic system has proven to be effective in creating prosperity. Through the presentation of this article, it is hoped that efforts to create prosperity as well as equalize welfare will always be pursued through the application and contextualization of a proven and tested economic system.